2013
DOI: 10.1128/cvi.00738-13
|View full text |Cite
|
Sign up to set email alerts
|

Novel Catanionic Surfactant Vesicle Vaccines Protect against Francisella tularensis LVS and Confer Significant Partial Protection against F. tularensis Schu S4 Strain

Abstract: g Francisella tularensis is a Gram-negative immune-evasive coccobacillus that causes tularemia in humans and animals. A safe and efficacious vaccine that is protective against multiple F. tularensis strains has yet to be developed. In this study, we tested a novel vaccine approach using artificial pathogens, synthetic nanoparticles made from catanionic surfactant vesicles that are functionalized by the incorporation of either

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
32
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 77 publications
1
32
0
1
Order By: Relevance
“…We previously showed that F. tularensis antigens detected by LVS-V-or Schu S4-V immune sera in Western blot analyses are highly conserved across the major evolutionary clades of F. tularensis strains (25). We next asked whether the addition of MPL adjuvant enhanced the detection of either the same or additional F. tularensis antigens.…”
Section: Immunization Of Mice With Lvs-v Elicits Serummentioning
confidence: 99%
See 4 more Smart Citations
“…We previously showed that F. tularensis antigens detected by LVS-V-or Schu S4-V immune sera in Western blot analyses are highly conserved across the major evolutionary clades of F. tularensis strains (25). We next asked whether the addition of MPL adjuvant enhanced the detection of either the same or additional F. tularensis antigens.…”
Section: Immunization Of Mice With Lvs-v Elicits Serummentioning
confidence: 99%
“…While immunization with LVS-V protected fully and was associated with high serum titers of IgG, significant partial protection was gained through immune stimulation with the empty V, despite an absence of IgG and cytokine production. This suggested that the V possess intrinsic innate immune stimulatory activity (25). To determine the efficacy of LVS-V nanoparticles to protect against respiratory tularemia, which has a more severe clinical presentation, we tested this vaccine in an i.n.…”
Section: Immunization Of Mice With Lvs-v Elicits Serummentioning
confidence: 99%
See 3 more Smart Citations